Child abuse and all-cause mortality in the Canadian population. (30th September 2020) - Bhattarai, A; Dimitropoulos, G; Williams, J; Bulloch, A; Patten, S
Abstract: Background: A history of child abuse is common and is associated with the later occurrence of risky health behaviors, mental disorders, and chronic conditions, strongly suggesting that child abuse may be associated with elevated mortality. However, most of the literature on child abuse has studied psychosocial/behavioral or medical outcomes and have not addressed mortality directly. Methods: Data from the 2012 Canadian Community Health Survey, linked to the Canadian Vital Statistics Database, were used in the analysis. The CCHS-2012 interview (n = 19, 830) retrospectively assessed childhood physical abuse, sexual abuse, and witnessing intimate partner violence before the age of 16. Each type of abuse was analyzed separately using Cox proportional hazards models for all-cause mortality. Hazard ratios (HR) and associated 95% confidence intervals (CI) were estimated with and without adjustment for covariates. Results: An effect on mortality was observed among men for witnessing interpersonal violence (age-adjusted HR 2.47, 95% CI 1.48-4.12), and severe physical abuse (age-adjusted HR 2.3, 95% CI 1.21-4.36). In each case, the association was not significant for women; the age-adjusted HRs being 0.93 (95% CI: 0.51-1.70) and 0.59 (95%CI: 0.64-2.60) respectively. The association was seen only among those reporting frequent abuse ( > =10 times) and weakened (became not significant) with adjustment for covariates that may mediate the association such as smoking and chronic conditions. Conclusions: As predicted by a broader literature on childhood adversity, child abuse increases the risk of mortality. The effect was significant for severe physical abuse in men, but imprecision due to a limited number of deaths may have rendered other associations non-significant. The study provides some degree of confirmation that child abuse contributes to later life mortality. Hence public health strategies that prevent child abuse and mitigate the harms of the mediators might prevent mortality. Key messages: Witnessing intimate partner violence is just as harmful as actually experiencing physical abuse. Preventing children's exposure to violence in family is valuable in preventing mortality in adulthood. Enhancing child abuse prevention programs and mitigating the harmful effects of the mediators such as smoking, substance use, and chronic conditions is important in reducing mortality in adult life.